FRI0418 In vitro effects of ctla4-ig treatment on cultured fibrocytes from systemic sclerosis patients. (12th June 2018) - Cutolo, M.; Montagna, P.; Soldano, S.; Trombetta, A.C.; Ruaro, B.; Contini, P.; Sulli, A.; Scabini, S.; Stratta, E.; Brizzolara, R.
Abstract : Background: Circulating fibrocytes (CFs) are progenitor cells derived from bone marrow, expressing markers of both hematopoietic cells (CD45, MHC class II) and stromal cells (collagen I and III), together with the chemokine receptors, which regulate their migration into inflammatory lesions (CXCR4, CCR2, CCR7). 1 CFs can migrate into SSc-affected tissues and can differentiate into fibroblasts/myofibroblasts. 2 CFs express the CD86 (B7.2) costimulatory molecule and the adhesion molecules CD11a, CD54, ICAM-1, and CD58. The fusion molecule CTLA4-Ig interacts with CD86 and can downregulate the target cell. 3 Objectives: To study the in vitro effects of CTLA4-Ig on cultured CFs. Methods: CFs were obtained from the peripheral blood samples of 8 "limited" cutaneous SSc patients (treated only with vasodilators, mainly cyclic prostanoids) and from 4 healthy subjects (HSs). CFs were characterised by fluorescence-activated cell sorter analysis (FACS), at basal time (T0) and after 8 culture days (T8), for CD45, collagen type I (COL I), CXCR4, CD14, CD86, and HLA-DRII expression. T8-cultured CFs were treated for 3 hours in the absence or in the presence of CTLA4-Ig (10, 50, 100 and 500 micrograms/ml). Quantitative real-time polymerase chain reaction (qRT-PCR) for CD86, COL I, IL1b, TGFb, αSMA, S100A4, CXCR2, CXCR4, CD11a were performed. The statistical analysis was carried out by the nonparametric Mann-Whitney U test. Skin samples for fibroblast (SFs) cultures were obtained from the same patients after EC and patient informed consent. Results: At qRT-PCR, T8-SSc fibrocytes, in the absence of CTLA4-Ig treatments, showed higher CD86 expression levels compared to HSs fibrocytes. Similarly also αSMA, S100A4, TGFb and COL I gene expression resulted higher in SSc fibrocytes compared to HSs. After CTLA4-Ig treatments, only in SSc fibrocytes, the αSMA and COL I gene expression resulted significantly decreased (p<0.01, p<0.05), whereas the gene expression for S100A4 resulted significantly increased (p<0.01), compared to untreated fibrocytes. Interestingly, in skin fibroblasts from the same SSc patients, the CD86 gene expression was found to be very low, compared to CFs. Conclusions: Circulating fibrocytes from patients affected by limited cutaneous SSc seem to be responsive and downregulated after in vitro CTLA4-Ig treatments, suggesting a possible antifibrotic effect on progenitor cells before their final homing and differentiation in active myofibroblasts. Fibroblasts from the same patient do not show the same expression of target molecules and reactivity to CTLA4-Ig. References: [1] Bucala R. Mol Med2015;2:S3–5. [2] Keeleya EC, et al. The International Journal of Biochemistry & Cell Biology2010;42:535–42. [3] Cutolo M, et al. Arthritis Res Ther2009;11:176–85. Disclosure of Interest: M. Cutolo Grant/research support from: BMS, Actelion, Celgene, Boehringer, P. Montagna: None declared, S. Soldano: None declared, A. C. Trombetta: None declared, B. Ruaro: None declared, P. Contini: None declared, A. Sulli: None declared, S. Scabini: None declared, E. Stratta: None declared, R. Brizzolara: None declared